Pruritus ani – aetiology and treatment - Hadasik, Karolina; Hadasik, Grzegorz; Brzezińska-Wcisło, Ligia (Dermatology Review/Przegląd Dermatologiczny, 2011)
Perianal pruritus is an unpleasant cutaneous sensation that induces scratching of the skin around the anal orifice. It is a common symptom in the course of many systemic, dermatological and proctological disorders. The diagnosis of pruritus ani may be challenging because of the anatomical and physiological condition in the anorectal area. When no apparent cause is present we use the term idiopathic pruritus ani. In this article we present the most common causes of perianal itch and its therapy and idiopathic pruritus ani with its management possibilities.